A variant of a type V lateral clavicle fracture involving a posteriorly displaced medial segment. A case report - Goss Thomas P; Li Xinning (BMC, 2012)
Abstract The clavicle connects the shoulder girdle to the axial skeleton, providing support and mobility for optimal upper extremity function. Fractures of the clavicle account for up to 4% of all fractures and comprise up to 44% of all injuries to the shoulder girdle. We present a 63-year-old female patient who suffered what appeared to be a minimally displaced Type V lateral clavicle fracture after a fall as evidenced by an anteroposterior shoulder radiograph. However, an axillary projection demonstrated the proximal segment to be posteriorly displaced and buttonholed through the trapezius musculature with tenting of the skin. The patient underwent an open reduction and Kirschner wire fixation of the fracture with complete healing, subsequent removal of the hardware and return to her previous level of function six months following surgery. After an extensive literature search, we believe this is the first case report documenting a variant of a Type V lateral clavicle fracture, specifically with significant posterior displacement of the proximal segment, mimicking a Type IV AC separation. This fracture pattern is unstable and represents a double disruption of the superior shoulder suspensory complex. Surgical management was successful in returning our patient back to her previous activity of daily living.